PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS DAN LIKUIDITAS TERHADAP VOLATILITAS HARGA SAHAM PERIODE 2020-2022 - Supraptiningsih; Ahadiati Rohmatiah; Ridho Rodhiansyah (Universitas Merdeka Madiun, 2025)
This research aims to determine the influence of dividend policy, profitability, and liquidity variables on stock price volatility, examining both partial and simultaneous effects. The results of this research can provide benefits in examining understanding and increasing insight into the influence of dividend policy, profitability, and liquidity on stock price volatility. The type of research used in this study is an associative approach. This research employs purposive sampling as the sampling technique. The population studied consists of 62 mining sector companies listed on the Indonesian Stock Exchange. The sample used in this study consists of 18 mining companies listed on the Indonesia Stock Exchange. The type of data used in this study is quantitative data in the form of secondary data. The data used in this study were obtained from the Indonesia Stock Exchange and the websites of companies related to the annual period, specifically the years 2020–2022. This study utilizes secondary data sources, specifically a list of companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. The research instruments for this study are documentation and a literature review to access the annual financial reports of mining companies. Based on the results of this study, the variables Dividend Payout Ratio, Return On Assets, and Current Ratio have a negative and significant partial effect on stock price volatility, while simultaneously having a positive and significant effect on stock price volatility.